Case study on the influence of synoptic-scale processes on the paired H2O-O3 distribution in the UTLS across a North Atlantic jet stream - Schäfler, Andreas; Sprenger, Michael; Wernli, Heini; Fix, Andreas; Wirth, Martin (Copernicus Publications, 2022)
During a research flight of the Wave-driven ISentropic Exchange (WISE) campaign, which was conducted over the eastern North Atlantic on 1 October 2017, the composition of the Upper Troposphere and Lower Stratosphere (UTLS) across the North Atlantic jet stream was observed by airborne, range-resolved Differential Absorption Lidar (DIAL) profiles. We investigate how the high variability in the paired H2O and O3 distribution along the two-dimensional lidar cross section is affected by synoptic-scale weather systems, as revealed by the Lagrangian history of the observed air masses. To this aim, the lidar observations are combined with 10-day backward trajectories along which meteorological parameters and derived turbulence diagnostics are traced. The transport and mixing characteristics are then projected to the vertical cross sections of the lidar measurements and to the H2O–O3 phase space to explore linkages with the evolution of synoptic scale weather systems and their interaction. Tropical, midlatitude and arctic weather systems in the region of the jet stream and the related transport and mixing explain the complex H2O and O3 distribution to a large extent: O3-rich stratospheric air from the high Arctic interacts with midlatitude air from the North Pacific in a northward deflected jet stream associated with an anticyclone over the US and forms a filament extending into the tropopause fold beneath the jet stream. In the troposphere, lifting related to convection in the innertropical convergence zone (ITCZ) and two tropical cyclones continuously injected H2O into dry descending air from the tropical Atlantic and Pacific forming filamentary H2O structures. One tropical cyclone that transitioned into a midlatitude cyclone lifted moist boundary layer air explaining the highest tropospheric H2O values. During the two days before the observations the air with mixed tropospheric and stratospheric characteristics experienced frequent turbulence along the North Atlantic jet stream indicating a strong influence of ...